2021
DOI: 10.5599/jese.1099
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring surface properties of functionalized graphene papers aiming to enzyme immobilization

Abstract: The use of enzymes as catalysts requires recovery and reuse to make the process viable. Enzymatic immobilization changes enzyme stability, activity, and specificity. It is very important to explore new substrates for immobilization with appropriate composition and structure to improve the efficiency of the immobilized enzymes. This work explores the use of two different graphene oxide papers, one produced by oxidation route (GO) and the other by electrochemical synthesis (EG), aiming for β-galactosidase immobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The surface morphologies of the EG and GO papers were analyzed by SEM. The SEM image of the EG sheet, Figure 2A, shows a crumpled texture typical of exfoliated graphene sheets [23]. By contrast, the SEM image of GO paper, Figure 2C, shows a smooth surface.…”
Section: Morphological Characterizationmentioning
confidence: 97%
See 1 more Smart Citation
“…The surface morphologies of the EG and GO papers were analyzed by SEM. The SEM image of the EG sheet, Figure 2A, shows a crumpled texture typical of exfoliated graphene sheets [23]. By contrast, the SEM image of GO paper, Figure 2C, shows a smooth surface.…”
Section: Morphological Characterizationmentioning
confidence: 97%
“…In these images, one can see typical wrinkles of graphene and some higher regions (120 nm for both GO and EG), indicating that both papers have regions with different numbers of graphene layers stacked on top of each other. EG is known to have significant heterogeneity and may be more oxidized/exfoliated in some parts than others, presenting some non-oxidized/non-exfoliated regions such as the original graphite [23]. Topography heterogeneity as well as different types of defects (edge defects, vacancies, functional groups, heteroatoms) in graphene sheets, mainly generated by the electrochemical oxidation and exfoliation processes, may generate electrical mobility, explaining the higher electrical conductivity of EG papers when compared to GO papers, as observed in I-V curves, Figure 3.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…Among the advantages of paper, some can be highlighted for electrochemical biosensing applications, on which we are focused in this article. For example, the intrinsic properties of paper, e.g., the fibrous and porous 3D structure of cellulose fibers, can lead to: a) higher absorption for effective storage (e.g., in antibody, aptamer or enzyme modifications) and delivery of samples which can lead to the increased sensitivity, faster response time and accuracy of time-dependent measurements [30][31][32]; b) elimination of air bubbles, which is beneficial in sensors especially in microfluidics [21]; c) large specific surface area to enhance the number of immobilized biomolecules [30,33,34]; d) elimination of a need for pumps and electrical power to transport fluids owing to its numerous capillaries [4,21,23,35,36]; e) better electrochemical detection by use of conductive inks easily deposited on paper [37] , and f) detection with just very low volumes of samples [37].…”
Section: Strategies For Choosing a Paper Substratementioning
confidence: 99%
“…Filter, chromatographic and office papers are the most widely utilized substrates for ePADs. Among them, Whatman #1 paper is the most extensively used in laboratories, probably due to its availability, excellent wicking ability and absorption of more aqueous solution by a dry filter paper [34,47]. For more information, one can refer to the recent review research reported by Desmet et al with detailed information on the diffusion coefficient values of analytes with ePADs made of different types of paper, especially Whatman paper, a comparison of the reported values in solution, the amount of water absorbency by the paper, and the electrochemical techniques used to determine these values [35].…”
Section: Strategies For Choosing a Paper Substratementioning
confidence: 99%
“…In the paper by Pereira et al [15], the development of multiwalled carbon nanotube ink was described for its application in electrochemical sensors, and in the paper by Araujo et al [16], graphene papers were functionalized to increase the efficiency of enzyme immobilization.…”
mentioning
confidence: 99%